Comparison of risk of cardiovascular disease related adverse events between selective serotonin reuptake inhibitor users and serotonin norepinephrine reuptake inhibitor users in Korean adult patients with depression: retrospective cohort study. (April 2021) - Park, Kyounghoon; Kim, Seonji; Ko, Young-Jin; Park, Byung-Joo
Highlight: identified cardiovascular disease-related adverse events risk of serotonin norepinephrine reuptake inhibitor (SNRI) comparing to selective serotonin reuptake inhibitor (SSRI) the cohort study using Korea Health Insurance Review and Assessment data (2008~2018) with high-dimensional propensity score method No significant hazard ratio was found between SNRI and SSRI for the three CVD-related adverse events Subgroup analysis showed a high risk of hemorrhagic stroke in SNRI users with hypertension and diabetes mellitus Abstract: Serotonin norepinephrine reuptake inhibitor (SNRI) has been increasingly administered, but the associated cardiovascular disease (CVD) related adverse events risk is not clearly understood. So, we conducted a cohort study to identified CVD-related adverse events risk of SNRI comparing to selective serotonin reuptake inhibitor (SSRI). We used Korea Health Insurance Review and Assessment data. During the period from April 2009 to March 2011, patients who were prescribed SSRI or SNRI for depression, who were followed up till March 2018, were the subjects. Hemorrhagic stroke, ischemic stroke, and myocardial infarction were selected as the outcomes. High-dimensional propensity scores were used to adjust the unmeasured confounders. the cox proportional hazard model was used for the statistical analysis. A total of 1, 016, 136 patients diagnosed with depression over the age of 20 were screened and there were 64, 739 SSRI users and 3, 711 SNRI users in the group of patients. The adjusted hazard ratio did not differ between the two groups, but the subgroup analysis according to comorbidities showed a high risk of hemorrhagic stroke in SNRI users with hypertension or diabetes mellitus.